KONSEPSI INTELEKTUALITAS, KEUANGAN, DAN MASSA DALAM PEMILIHAN BUPATI SIKKA TAHUN 2018 - ALFIAN HARBIYANTO (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Indonesia is a democracy. Where the election of the Regional Head (Regent) is directly elected by the people. The people have full rights to choose who the leader will lead an area. Elections are held in a direct, public, free and confidential manner. Election of regional head and deputy regional head, or often called local election or post-conflict local election, is a general election to elect regional heads and deputy regional heads directly in Indonesia by local residents who meet the requirements. Every people would want a leader who is intelligent, responsible and can be sensitive to problems that occur in the community itself. And it all can not be separated from what leaders do when they run. How they arrange strategies to be chosen and liked by the people. How do they communicate, how are they in a relationship and attract the attention of the people to how they arrange the concepts of finance and the masses in the election event. The purpose of this study was to find out how the Regional Head of Sikka Regency attracted the sympathy of the people to vote for him. This research was conducted with interview and observation techniques so that this research generates new knowledge for researchers that each Regional Head candidate has their respective strategies to be able to attract the attention of the people one of which is to conduct a campaign.